2017
DOI: 10.31274/ans_air-180814-497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Responses to Vaccination of Angus Cattle for Four Viruses that Contribute to Bovine Respiratory Disease Complex

Abstract: and Implications Initial antibody titers are maternally-derived from colostrum, then decay with age. Change in antibody titer levels were compared between four viruses contributing to the Bovine Respiratory Disease Complex (BRDC), and evaluation of response to vaccination indicated that antibody production will not occur when high levels of maternal antibodies are present. The maternal antibodies were found to decay with calf age for each of the four viruses, which allowed for the estimation of a maximum circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Downey et al, 2013 demonstrated that the decay rate of maternal antibodies is rather low and that there is a threshold effect: the calves do not respond to the vaccine if the level of maternal antibodies exceeds a threshold and only respond when this level drops. Also, the impact of calf age on antibody response (titers) to BRD was previously shown to be insignificant (Kramer et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Downey et al, 2013 demonstrated that the decay rate of maternal antibodies is rather low and that there is a threshold effect: the calves do not respond to the vaccine if the level of maternal antibodies exceeds a threshold and only respond when this level drops. Also, the impact of calf age on antibody response (titers) to BRD was previously shown to be insignificant (Kramer et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For each animal, four IgG samples were collected: three weeks prior to vaccination (referred to as "-3"), at the moment right after the first vaccination (referred to as "0"), three weeks postvaccination (referred to as "+3"), and six weeks post-vaccination (referred to as "+6"). Serum from each of the sequenced animals was also assayed for BRD-specific antibody titers at the same time points (Kramer et al, 2017) to quantify pre-existing immunity (e.g., resulting from maternal antibodies that are passed through milk from the mother to the child) and as a measure of vaccine success.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations